(untitled) (Revista LIDER, 2020)
We analyze the connection tourisminsecurity using a perspective of selforganized holarchic open systems; as we explore it, the scales involved and the elements which make it possible appear in a position that shows the reaches of supranational phenomena in the local/regional expression of the conditions necessary for sustainable tourism development. With it many doubts arise on the real possibilities to offer security in the face of locally or regionally respond to a global-scale phenomenon, and the challenging to the holistic character of STD.